U.S. Agricultural Commodity Organizations' Use of Blogs as a Communications Tool - Madeline L. Moore; Courtney Meyers; Erica Irlbeck; Scott Burris (Journal of Applied Communications, 2015)
Current communications trends and social media have given individuals and organizations unprecedented opportunities to build relationships with audience members while introducing and encouraging new perspectives. One particular form of social media is blogging, which allows people to share a wider variety of information than other forms of social media. The purpose of this study was to explore how agricultural commodity organizations use blogs as a communication tool. The researchers purposively selected nine U.S. agricultural commodity groups that had an organizational blog and collected data through in-depth interviews. The findings indicated the organizations started blogging because blogs were the newest communication tool they could use to reach new and traditional audiences. The commodity organizations used some online analytics and mentions on other social media outlets to measure blog success, but they did not establish goals for their blog prior to the blog’s launch. The findings offer an understanding of how agricultural commodity organizations are utilizing blogs, which provides insight for others in the agricultural industry who may decide to use this technology.
Keywords: Social media; online communication; farmers; ranchers